Nut size and color and shade affect germination of Quercus deserticola - Rodríguez-Trejo, Dante Arturo; Pompa-García, Marín (Instituto de Ecología, A.C., 2016)
Mexico is the country with the highest number of Quercus species worldwide (157). The oaks have great ecological importance and economic potential. However, their seeds and nursery propagation have been scarcely studied. The aim of this study was to investigate the effect of nut size and color, as well as shade, on germination of Quercus deserticola. The experiment was installed in a controlled environment chamber (25 °C/20 °C, with a photoperiod of 10 h of light). The experimental factors were nut size (small and large), color (light brown and dark brown), and shade (with and without 40% shade). The experimental design was completely randomized blocks, with the blocks nested into the shade factor. An analysis of variance with a mixed procedure and a Tukey means comparison were conducted, with the variables germinative capacity and germinative energy and a logistic model was constructed to estimate the probability of germination. There was a significant effect of seed size (p = 0.0067), seed color (p < 0.0001) and shade (p = 0.0078) on germinative capacity. The highest germinative capacity (100%) was for large seeds of dark brown color and under shade. The germinative energy (number of days to reach 70% of the germinative capacity) was affected by seed color (p < 0.0001) and by the interaction seed size*color (p = 0.0267). The highest germinative energy (11.5 days) was for large and dark brown colored seed.